KULTUR ARAB DALAM HADIS PEMIMPIN NEGARA DARI SUKU QURAYSH - Khoir, Moh. Misbakhul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2014)
This article wants to present a comprehensive discussion of related interventions arabic culture elements which to some extent has influenced the style of thinking and normal life of the Prophet in the hadith leaders expressed in the State of Quraysh. This is given in addition to as an Apostle, Muhammad also serves as head of state, warlords, judges, community leaders, husband and personal. As an Arab man who lives in the community and the arabic culture, the environment and the interaction with the surrounding culture has its own influence on the habits and behavior. Consequently, what comes from the Prophet Muhammad must exist in between which is the culture of Arab societies at the time. Hadith state leaders of Quraysh, for example, is a statement of the Prophet Muhammad based on considerations of arabic culture at that time. Socio-historical, Quraysh is a decent clan inherited the throne of leadership, due to the advantages that are not found in other ethnic groups at the time. Thus, the actual terms of the Quraysh merely symbolic terms.